VD_FINDINFO AI 24/09 - 271/2011 vom 19. Mai 2011 - VD Tribunal cantonal (2011)
AIASSURANCE, RENTEEN GÉNÉRAL, NOUVELLE DEMANDE, DÉDUCTIONSENS GÉNÉRAL | 28 LAI, 4 LAI, 16 LPGA, 6 LPGA, 7 LPGA, 8 LPGA, 87 RAI